CTNI-18. FIRST MULTICENTRIC REAL-LIFE EXPERIENCE WITH THE COMBINATION OF CCNU AND TEMOZOLOMIDE IN NEWLY DIAGNOSED MGMT PROMOTER METHYLATED IDH WILDTYPE GLIOBLASTOMA. (14th November 2022) - Lazaridis, Lazaros; Bumes, Elisabeth; Spille, Dorothee Cäcilia; Schulz, Tim; Heider, Sina; Agkatsev, Sarina; Schmidt, Teresa; Blau, Tobias; Oster, Christoph; Feldheim, Jonas; Stummer, Walter; Kessler, Almuth Friederike; et al.
Abstract: BACKGROUND: The randomized phase 3 CeTeG/NOA-09 trial assessed whether CCNU plus temozolomide was superior to temozolomide alone in newly diagnosed MGMT promoter methylated glioblastoma patients. Survival was significantly improved from 31.4 months (temozolomide) to 48.1 months (CCNU plus temozolomide). In view of this encouraging data, we assessed safety and efficacy of this regimen under real-life conditions. METHODS: We retrospectively collected clinical and radiographic data from adult newly diagnosed MGMT promoter methylated IDH wildtype glioblastoma patients from five neuro-oncology centers in Germany. For inclusion in our analysis, treatment with CCNU and temozolomide had to be performed for at least six weeks (one course). RESULTS: Seventy patients were included. Median progression-free survival was 14.4 months and median overall survival 33.8 months. Patients with TTFields treatment for at least eight weeks and CCNU plus temozolomide (n = 22, 31%) had a prolonged progression-free survival compared to those with TTFields treatment for less than eight weeks (n = 48, 69%) (21.5 versus 11.2 months; p = 0.0105). In a multivariable Cox regression analysis, TTFields treatment for eight weeks or longer together with CCNU plus temozolomide and a Karnofsky performance score ≥ 90% were independent prognostic factors for progression-free and overall survival. Pseudoprogression occurred in n = 16 (33%) of investigated n = 49 (70%) patients. In n = 31 (44%) patients high-grade hematotoxicity was observed. CONCLUSIONS: The results from this multicentric trial indicate - under real-life conditions - toxicity and survival estimates comparable to the CeTeG/NOA-09 trial. TTFields therapy for at least eight weeks in combination with this regimen was independently associated with prolonged survival.